2015
DOI: 10.1093/ntr/ntu337
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Dependence, Nicotine Metabolism, and the Extent of Compensation in Response to Reduced Nicotine Content Cigarettes

Abstract: Introduction: The Food and Drug Administration has the authority to regulate tobacco product constituents, including nicotine, to promote public health. Reducing the nicotine content in cigarettes may lead to lower levels of addiction. Smokers however may compensate by smoking more cigarettes and/or smoking more intensely. The objective of this study was to test whether individual differences in the level of nicotine dependence (as measured by the Fagerstrom Test of Cigarette Dependence [FTCD]) and/or the rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
3

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 28 publications
0
30
0
3
Order By: Relevance
“…According to the same quartile system, the slowest metabolizers had lower nicotine dependence, reported less cigarette craving following overnight abstinence, and less drug liking after intravenous nicotine compared to the fastest metabolizers (Sofuoglu et al, 2012). While NMR (considered as a continuous variable) was not associated with decreases in nicotine dependence produced by smoking reduced-nicotine cigarettes over 6 months in one study (Bandiera et al, 2015), the interaction of nicotine dose and NMR on the acute effects of smoking are unknown.…”
Section: Introductionmentioning
confidence: 96%
“…According to the same quartile system, the slowest metabolizers had lower nicotine dependence, reported less cigarette craving following overnight abstinence, and less drug liking after intravenous nicotine compared to the fastest metabolizers (Sofuoglu et al, 2012). While NMR (considered as a continuous variable) was not associated with decreases in nicotine dependence produced by smoking reduced-nicotine cigarettes over 6 months in one study (Bandiera et al, 2015), the interaction of nicotine dose and NMR on the acute effects of smoking are unknown.…”
Section: Introductionmentioning
confidence: 96%
“…Understanding the factors that contribute to compensation and its individual variability is important to anticipate the differential risk for this potential side effect of nicotine reduction between vulnerable subpopulations, and to identify supportive interventions they may need to minimize it. For instance, a recent study showed that the level of nicotine dependence as indicated by time to smoke the first cigarette of the day (but not the Fagerstrom Test of Cigarette Dependence score) is positively correlated with degree of compensation (Bandiera et al, 2015), suggesting that smokers who are more dependent may be at greater risk of compensation.…”
Section: Introductionmentioning
confidence: 99%
“…Using methods demonstrated by Sell and colleagues (Sell et al, 2016), a series of step-wise regression models examined the direct effects of post-advertisement false beliefs and initial (i.e., only the single assessment from Day 5) subjective ratings on mean smoking behaviors, and the moderating effect of subjective ratings on the association between beliefs and behaviors (Figure 1). In the first step of regression models, each smoking behavior (e.g., daily RNC consumption) was regressed onto covariates identified a priori for their potential effects on study outcomes, including: gender (Perkins, 1996; Perkins et al, 1999; Vogel et al, 2014), BMI (Blendy et al, 2005) nicotine dependence (Bandiera et al, 2015), years smoking (Ayanian and Cleary, 1999), and cigarette type (Kozlowski and Pillitteri, 2001). To account for increased consumption of Quest cigarettes relative to participants’ own preferred brand cigarettes (Mercincavage et al, 2016), daily consumption of own brand during the 5-day baseline period was also included as a covariate.…”
Section: Methodsmentioning
confidence: 99%
“…Smokers can “compensate” for such design features to increase nicotine intake by modifying their smoking behaviors (e.g., increasing daily consumption, blocking filter vents), increasing intake of other, harmful constituents (USDHHS, 2001). In contrast, little to no compensation occurs with long-term RNC cigarette use (Bandiera et al, 2015; Donny et al, 2015; Hatsukami et al, 2015; Mercincavage et al, 2016) because they contain insufficient extractable nicotine and do not reward these behaviors.…”
Section: Introductionmentioning
confidence: 99%